Research on colombian medicinal plants: roles and resources for plant taxonomists (1986)
Colombia has one of the richest floras of any country on earth. It has a large topographic range and varied climatic regimes, and is rich in endemic species (GENTRY, 1983). Many areas of the country have been poorly collected; nevertheless, SCHULTES (1951) estimates that 50.000 species of phanerogams grow in Colombia. PRANCE (1977) cites the lower figure of 45.000, and other workers have speculated that the diversity is even lower (GENTRY, 1978). Because the study of the flora of Colombia is not yet complete it is impossible to give an accurate figure for the number of plant species occurring in the country. It is certain, however, that Colombia is tremendously rich floristically, including in its flora perhaps as much as 50% of all the flowering plant species in the Neotropics (PRANCE, 1977).